1998
DOI: 10.1243/1350650981542001
|View full text |Cite
|
Sign up to set email alerts
|

Elastohydrodynamic analysis of one-layered journal bearings

Abstract: Steady state and dynamic solutions to the problem of isothermal elastohydrodynamic lubrication of single-layered journal bearings are derived and presented. The mathematical problem comprises two parts: fluid and elasticity. The elasticity problem is governed by the elastostatic equations which are solved by application of a complex variable approach using the complex Kolosov-Muskhelishvili potentials. The fluid problem is described by the two-dimensional Reynolds equation which is discretized using a finite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Note that the cross-coupling damping coefficients B XY and B YX , unlike the corresponding stiffness coefficients, are equal. However, these coefficients become different when the dynamic deformation of the bearing-liner is considered in addition to the static deformation [29,34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the cross-coupling damping coefficients B XY and B YX , unlike the corresponding stiffness coefficients, are equal. However, these coefficients become different when the dynamic deformation of the bearing-liner is considered in addition to the static deformation [29,34].…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier work [29], we have demonstrated that the general solutions of planeelastostatics problems for a circular ring can be expressed in a complex Fourier series as given below.…”
Section: General Solutions Of Plane Elastostaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the additional condition ε R << 1 is correct, then the displacement of the liner surface w can be defined as [7,8] …”
Section: Design Model Onementioning
confidence: 99%
“…Some studies have examined the effect of bearing liner deformation on the slider bearing characteristics (e.g., the pressure distribution, load carrying capacity, and frictional force) [16,17,18,19,20,21,22] and they indicated that the elastic parameter could strongly affect the friction coefficient and the flow rate. Others focused on the impact of the journal eccentricity perturbation or the journal misalignment and the rheological effects of couple stress fluids on stiffness and dynamic coefficients of finite journal bearing with the elastic bearing shell, such as gas foil bearing, offset-halves pressure dam bearing, coupled journal-thrust bearing [23,24,25,26,27,28,29]. Another aspect of the research of elastic bearing properties is that of viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%